Utilisation patterns of home care services of long-term care programmes and primary caregivers' workload in Taiwan. Issue 1 (2nd January 2019) - Li, Yang-Tzu; Chang, Hong-Jer; Lin, Yu-Hung; Cheung, Johnson Chun-Sing; Pak, Chui-Man; Tsui, Ming-Sum
ABSTRACT: This study examines service utilisation patterns and investigates the needs and barriers to service utilisation among users and non-users of home care services in Taiwan. 450 participants were selected based on the ratio of clients in the institution to the total number of care recipients in Taipei City. This study shows that about 30% of the participants had experienced a gap between approved and actual service hours. The results of three multiple regression analyses also confirm the significance of a gap in housekeeping and physical care services, suggesting that more attention should be paid to a number of critical factors.